EFFECT OF NITROGEN FERTILIZATION ON YIELD AND CHIPPING QUALITY OF PROCESSING VARIETIES GROWN IN COOLER NORTH INDIAN PLAINS - Sandhu, K S; Chinna, G S; Marwaha, R S; Kumar, Parveen; Pandey, S K. (Potato Journal, 2013)
A field study was conducted during 2006-07 and 2007-08 at amritsar (coolest place in north-western indian plains) with three processing varieties consisting of one indian variety Kufri chipsona-1 and two non-indian varieties viz., atlantic and Lady rosetta along with one indian table variety Kufri pukhraj to evaluate total and processing-grade tuber (>45 mm tuber diameter) yield and quality characteristics at four nitrogen levels (0, 100, 200 and 300 kg n/ha). Kufri pukhraj produced maximum total and processing grade tuber yield, but its processing quality was not acceptable. all the three processing varieties produced acceptable colour quality chips at all the levels of nitrogen application. among processing varieties, Kufri chipsona-1, although produced highest total tuber yield, the processing grade tuber yield was maximum in atlantic. There was an increase in total and processing grade tuber yield with nitrogen application up to 200 kg n/ha. chip colour darkened with the application of nitrogen, while dry matter content and tuber flesh firmness were maximum at 200 kg n/ha. The contents of reducing sugars, sucrose, free amino acids and total phenols increased with nitrogen application. Based on processing grade tuber yield and quality parameters, 200 kg n/ha was the optimum dose and atlantic was the most suitable variety followed by Kufri chipsona-1.